2020
DOI: 10.18438/eblip29721
|View full text |Cite
|
Sign up to set email alerts
|

Gathering Evidence of Learning in Library Curriculum Center Spaces with Web GIS

Abstract: Objective –This article reports on a pilot research project that gathered usage statistics in specifically designated library learning spaces using a Web-based Geographic Information System (GIS). These learning spaces were then mapped to expected learning activities that would occur in these areas based on its intention or design. In this way, the library could begin to associate the usage of a space with different types of learning. The researchers then mapped these learning activities to campus learning out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Most of the WebGIS based dashboards have been developed to support urban management but little work has been carried out for conservation of soil and water. The new managerialism involves citizens who generate geospatial data, interact collaboratively with the government (Spyratos et al, 2014), and look for evidencebased decision-making (Kitchin, 2016a;Stoddart & Godfrey, 2020). Therefore, these characteristics of new managerialism result in the need for geospatial dashboards to support soil and water management.…”
Section: Web-gis Architecturementioning
confidence: 99%
“…Most of the WebGIS based dashboards have been developed to support urban management but little work has been carried out for conservation of soil and water. The new managerialism involves citizens who generate geospatial data, interact collaboratively with the government (Spyratos et al, 2014), and look for evidencebased decision-making (Kitchin, 2016a;Stoddart & Godfrey, 2020). Therefore, these characteristics of new managerialism result in the need for geospatial dashboards to support soil and water management.…”
Section: Web-gis Architecturementioning
confidence: 99%
“…In a study by Teel (2013), student consultations revealed the need for improvement in physical space and technology in their curriculum materials centre and importantly, a preference for the centre to relocate to the Faculty of Education building. A more recent study by Stoddart and Godfrey (2020) examined space usage in a newly renovated curriculum centre housed in the education building. They identify the most frequently used spaces in order to better understand the centre's contribution to "campus learning", and emphasize the importance of connecting library design to program and university learning outcomes.…”
Section: Convenience and Proximitymentioning
confidence: 99%